The call for an “educational footprint” in conceptualizing mental health and psychosocial support: the case of Norwegian kindergarten teachers - Christensen, Ingrid R. (Frontiers in Psychology, 2024)
This article presents an in-depth qualitative case study asking, “How do Norwegian kindergarten teachers conceptualize and negotiate the field of psychosocial support?” This article thoroughly explores how Norwegian kindergarten teachers perceive of the field Mental health and psychosocial support (MHPSS). Recognizing the global imperative to advance mental health and psychosocial support for children, the study highlights the crucial need for interprofessional grounded concepts and logics in developing MHPSS interventions. The study employs a grounded theory approach to actively develop concepts in the MHPSS field in Norway. The six selected Norwegian expert teachers can make up a so-called “unique case”, representing a high-income country with a robust welfare system and child-centered pedagogy. Yet, they reveal challenges in embracing the concept of psychosocial support: The analysis shows that the teachers seem to neglect and even reject the concept of psychosocial support, while also expressing inferiority and lack of agency towards other professions. However, the teachers also express the desire for more knowledge, and with proudness they energetically engage in fostering children’s agency and functioning by their everyday descriptions of «meeting with the child». The study calls for the kindergarten teachers’ increased efforts to actively participate in MHPSS interventions, advocating for the further development of an «educational footprint» that can empower interprofessional work.